2017
DOI: 10.1039/c7ta02022h
|View full text |Cite
|
Sign up to set email alerts
|

The potential of non-aqueous redox flow batteries as fast-charging capable energy storage solutions: demonstration with an iron–chromium acetylacetonate chemistry

Abstract: We report a fast-charging iron–chromium non-aqueous redox flow battery that combines the fast kinetics of the single iron(iii) acetylacetonate redox couple on the positive side with the fastest of the chromium(iii) acetylacetonate redox couple on the negative side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…The linear relationship between the peak current and the square root of the scan rates (Fig. 2c and d for NARFBs [16,22]. The solubility of both active species in 0.5 M TEATFSI/MeCN was measured by UV-Vis absorption spectra (Figs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The linear relationship between the peak current and the square root of the scan rates (Fig. 2c and d for NARFBs [16,22]. The solubility of both active species in 0.5 M TEATFSI/MeCN was measured by UV-Vis absorption spectra (Figs.…”
Section: Resultsmentioning
confidence: 95%
“…3a and b) exhibits rather stable cycling. The average CE, voltage efficiency (VE), and energy efficiency (EE) are 98.7%, 84.5%, and 83.4%, respectively, over 100 cycles, which are much higher than most non-aqueous systems [22,26]. The average discharge capacity is 1.50 Ah L -1 .…”
Section: Resultsmentioning
confidence: 95%
“…We hypothesize that this molecular rearrangement results in the reduction in k 0 for this event. Still, the kinetics for all four of the charge‐transfer events in Fe 4 Mo 4 O 16 are notably fast, a property which has positive implications on both the energy efficiency and power density of an RFB system . For the tungstate analogue, Fe 4 W 4 O 16 , the electron‐transfer rates are overall slower than those observed for Fe 4 Mo 4 O 16 , on the order of 10 −2− 10 −3 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Bamgbopa et al reported the first attempt at non-aqueous ICRFB containing Cr(acac) 3 and Fe(acac) 3 active species with TEABF 4 as the supporting electrolyte in 16 : 84 (vol %) 1,3dioxolane/acetonitrile. [43] The redox reactions are well-positioned to enable fast charging at up to 1.8 V, which is above the OCV (1.2 V). Further, the hydrogen evolution issue was not observed in this non-aqueous ICRFB.…”
Section: Electrolytesmentioning
confidence: 99%